2003
DOI: 10.1046/j.1432-1033.2003.03723.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cyr61/CCN1 gene expression through RhoA GTPase and p38MAPK signaling pathways

Abstract: Cysteine-rich protein 61 (Cyr61/CCN1) is an angiogenic factor and a member of a family of growth factor-inducible immediate-early genes with functions in cell adhesion, proliferation and differentiation. We investigated the regulatory mechanisms and signaling pathways involved in Cyr61/ CCN1 gene activation in smooth muscle cells. Treatment of these cells with sphingosine 1-phosphate (S1P), a bioactive lysolipid, increased rapidly but transiently the expression of the Cyr61/CCN1 gene at both the mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 61 publications
(72 reference statements)
6
85
1
Order By: Relevance
“…TRANSFAC analysis (Wingender et al, 2000) revealed that the AP-1-like element in the Cyr61/CCN1 gene promoter is a variant of the AP-1 consensus sequence (base À821 to À828) in which a single-base substitution of the center nucleotide has occurred (5 0 -TGACTCAG-3 0 ). Earlier studies showed that the AP-1 element has a critical role in regulating CCN1 promoter activity and hence CCN1 expression is tightly regulated through AP-1 transcription factors (Han et al, 2003). Mutation of the distal AP-1 element in the CCN1 promoter-reporter construct or overexpression of a dominant-negative AP-1 inhibitor reduced sphingosine 1-phosphate-induced CCN1 promoter activity by nearly 45% (Han et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRANSFAC analysis (Wingender et al, 2000) revealed that the AP-1-like element in the Cyr61/CCN1 gene promoter is a variant of the AP-1 consensus sequence (base À821 to À828) in which a single-base substitution of the center nucleotide has occurred (5 0 -TGACTCAG-3 0 ). Earlier studies showed that the AP-1 element has a critical role in regulating CCN1 promoter activity and hence CCN1 expression is tightly regulated through AP-1 transcription factors (Han et al, 2003). Mutation of the distal AP-1 element in the CCN1 promoter-reporter construct or overexpression of a dominant-negative AP-1 inhibitor reduced sphingosine 1-phosphate-induced CCN1 promoter activity by nearly 45% (Han et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that the AP-1 element has a critical role in regulating CCN1 promoter activity and hence CCN1 expression is tightly regulated through AP-1 transcription factors (Han et al, 2003). Mutation of the distal AP-1 element in the CCN1 promoter-reporter construct or overexpression of a dominant-negative AP-1 inhibitor reduced sphingosine 1-phosphate-induced CCN1 promoter activity by nearly 45% (Han et al, 2003). We documented that SARI exerts a cancer-specific antitumor effect by inhibiting AP-1 binding activity .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CCN1 is commonly overexpressed in GBMs, and its overexpression correlates with short survival time of GBM patients [22]. S1P has been shown to induce expression of CCN1 in smooth muscle cells [23]. We therefore, examined CCN1 protein levels in S1P receptor over-and underexpressing cell lines (Fig.…”
Section: Role Of Ccn1 In S1p-stimulated Invasionmentioning
confidence: 99%
“…Activation of the human CCN1 promoter was found to be regulated by CREB and activator protein 1 (AP-1) in sphingosine-stimulated smooth muscle cells (31) and by HIF and AP-1 following hypoxia in melanoma cells (21,22). The mouse CCN1 promoter was found to be activated by serum components via a serum response element at position À2 kb and an Egr binding site at position À48 bp (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%